The use of the arts expression in the museums of Bologna - Gómez Redondo, Carmen; Borghi, Beatrice (Clio. History and History Teaching, 2020)
The following article shows the results of an investigation on the use of plastic techniques in the educational programs of the museums of the city of Bologna. To this end, a specific tool has been designed to collect data on the use of plastic techniques in educational designs in the city’s museums, following the principles of cualitative method. After analyzing the data obtained, the main results of the study can be seen how museums incorporate plastic techniques in their designs, but mainly traditional techniques with a playful sense.